2018
DOI: 10.1111/iej.12891
|View full text |Cite
|
Sign up to set email alerts
|

Concentration‐dependent effect of bleaching agents on the immunolabelling of interleukin‐6, interleukin‐17 and CD5‐positive cells in the dental pulp

Abstract: IL-6 and IL-17 participated in inflammation in the pulp tissue of rats after tooth bleaching, particularly at 2 days. The immunolabelling was greater with increasing H O concentration. This process was accompanied by the prolonged activation of CD5-positive cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 41 publications
1
37
1
Order By: Relevance
“…Additionally, other studies have reported that IL‐17 is related to inflammatory events after bleaching procedures (Benetti et al . , Ferreira et al . ).…”
Section: Review Of Identified Publicationsmentioning
confidence: 99%
“…Additionally, other studies have reported that IL‐17 is related to inflammatory events after bleaching procedures (Benetti et al . , Ferreira et al . ).…”
Section: Review Of Identified Publicationsmentioning
confidence: 99%
“…, , Benetti et al . , ). The animals were housed in a temperature‐controlled environment (22 °C ± 1 °C, 70% humidity and a 12‐h light–dark cycle) and received water and food ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…or submitted to immunohistochemical analysis by using an indirect immunoperoxidase technique (Benetti et al . , Ferreira et al . ) for osteocalcin, osteopontin and ROS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations